Pengaruh Sistem Informasi Akuntansi Dan Peran Internal Audit Terhadap Kualitas Laporan Keuangan Pemerintahan Desa Pada Kecamatan Magepanda - Anastasia Febriana Ciciliawanti; Maria Nona Dince; Fransiscus De Romario (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this research is to examine and to analyze the influence of accountancy system utilization and the auditing internal role to the village government’s finance report quality of Magepanda Subdistrict. This kind of this research is quantitative research. The population in this research is the villages’device which located in 5 (five) villages in Magepanda Subdistrict, which the technique of sample taking use saturated sample, so the amount of sample in this research is 40 persons. The data which used in this research are primary data and secondary data which used the questionnaire as the data collection method. The data processing in this uses the SPSS software program. The result in this research shows that the accountancy system utilization (X1) and the auditing internal role (X2) take the partially effect of the finance report (Y) and the accountancy system utilization (X1) and the auditing internal role (X2) take the simultaneously effect to the finance report quality.